DEVELOPMENT EVALUATION AMONG FAMILIES OF PEOPLE WITH SUICIDAL BEHAVIOR: AN APPLICATION OF THE CALGARY MODEL - Andrade, Isabela Carolyne Sena de; Gomes, Nadirlene Pereira; Correia, Cíntia Mesquita; Romano, Cátia Maria Costa (Cogitare Enfermagem, 2024)
Objective: to describe the events that marked the development process experienced by families of people with suicidal behavior. Methodology: study based on the Calgary Family Assessment Model. The study had the participation of nine families of individuals who used the Suicide Study and Prevention Center located in the city of Salvador - Bahia, Brazil. Online data collection took place between November 2021 and May 2022. The questions were previously structured in a form based on the CFAM framework. Once transcribed, the interviews went through the transcreation and textualization processes. Results: among the categories that emerged, the following stand out: Experience of intra-family violence as a precipitating factor for suicidal behavior in the life cycle of the families; Self-renunciation in favor of caring for a person with suicidal behavior; and Animal bonding as a protective factor for suicidal behavior in the development process experienced by families of people with suicidal behavior. Conclusion: by elucidating such events, it is possible to connect with and intervene in the conflicts, as well as using them as protective factors against suicide attempts.